The forest code in small rural estates: a case study of three estates in Miringuava’s basin - Tourinho, Luiz Anselmo Merlin; Passos, Everton (UFPR, 2006)
Brazil is considered one of the countries with the most modernand comprehensive environmental legislation. However thislarge number of Laws creates difficulties for understandingand applying-them with efficiency and environmental returnfor society. This work is going to show that this confusion ofLaws complicates mainly the small rural estate to adapt itselfto the imposed norms, examples are the Forest Code (Law4.771, of 15-09-1965), the emergency measures that broughtit up to date and also the recurring changes in the statelegislation. It is discussed the problem of diverseinterpretations given to same points of imposed norms. Thestudy has assumed the importance of preserving theenvironment, but considers that this preservation can notoverrun the survival of the small rural producer, which in hisactivities should respect the environment even whentransforming his estate in a sustainable territorial unit infunction of the collective interest adapting itself to theenvironmental legislation, with incentives or feasiblealternatives to fulfill it. Among the main divergences ofinterpretation are the Legal Reserve and its forms ofcompensation. The present work seeks to show in an empirical form the applicability of this legislation and how much it interfereswith the rural estate. Three different estates were takenas study-object, in which were proposed incentives for theawareness and adaptation to the legislation and alsosuggestions for adapting to the norms.